Investigation on heat transfer characteristics and flow performance of methane at supercritical pressures - W. X., Hong; A. N., Oumer; F., Basrawi; R., Mamat; Abdul Adam, Abdullah (IOP Publishing, 2018)
Heat transfer and flow characteristics of cryogenic methane in regenerative cooling system at supercritical pressures has been determined numerically. Thermo-physical properties of supercritical methane are discussed. In addition to that, previous studies on experiment and simulation are reviewed. All geometry, related equations, boundary conditions and performance parameters are reviewed in detail. For mesh independence test and model validation, simulation results are compared to experimental work by Gu et al. (Gu, Li et al. 2013). It is found that simulation results show good agreement with experimental data. All data deviation lies within 10 % which is generally accepted by former researchers. The effects of four different performance parameters namely inlet pressure, inlet temperature, heat flux and mass flux on heat transfer and flow performance of supercritical methane in horizontal miniature tube are identified. Several results are generated based on experimental conditions which include inlet pressure of 5 to 8 MPa, inlet temperature of 120 to 150 K, heat flux of 2 to 5 MW/m2 and mass flux of 7000 to 15000 kg/m2s. Heat transfer performance factor and friction factor are then computed to obtain Goodness factor which optimum parameters for certain boundary conditions are chosen. Lastly, statistical analysis with Response Surface Method (RSM) is carried out to obtain regression for both heat transfer and pressure drop.